An evaluation of the distribution channel of nnf utama (m) sdn bhd - Isa, Nina Farisha; Mohd Yusoff, Norhayati; Ngelambong, Anderson (2011)
The emergence of internet enabled distribution channels has created both opportunities for and challenges to hotel's revenue management practices (Sun M.Choi & Kimes. E, 2002). Industries go through transformation with the introduction of new technology (Kostreva, 1990) as seen in the case of the service industry. Objective of the study is to evaluate the distribution system that currently being used by the budget hotel and to synthesis the employee's perception towards the global distribution system in hotel industry. A standard questionnaire were distributed to 120 respondents at budget hotel specifically. Quantitative analysis were conducted on the respondents demographic and perceptions of the employees about the hotel distribution system. The findings found 95% of the employees gives a positive respond about the electronic distribution system. In relation to distribution channel, most respondents had higher rate of convenience and efficient variables. As a result, the findings were to encourage budget hotel industry to implementing the global distribution system as it increase the hotel revenue and gives opportunities for the budget hotel to commercialize their products and services successfully. Therefore, this study achieve the main objective of evaluating budget hotel distribution channel in northern corridor economic region.